2017 4th International Conference on Computer Applications and Information Processing Technology (CAIPT) 2017
DOI: 10.1109/caipt.2017.8320692
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of real-time static hand gesture recognition using artificial neural network

Abstract: This paper implements static hand gesture recognition in recognizing the alphabetical sign from "A" to "Z", number from "0" to "9", and additional punctuation mark such as "Period", "Question Mark", and "Space" in Sistem Isyarat Bahasa Indonesia (SIBI). Hand gestures are obtained by evaluating the contour representation from image segmentation of the glove wore by user. Then, it is classified using Artificial Neural Network (ANN) based on the training model previously built from 100 images for each gesture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Results showed that the vision-based technique was more stable and reliable compared to the data glove-based technique. Hand gestures are obtained by evaluating the contour captured from the image segmentation using a glove worn by the speaker in Rosalina et al (2017). Also, in Danling, Yuanlong & Huaping (2016) they used a novel data glove called YoBu to collect data for gesture recognition.…”
Section: Gesture Acquisition Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results showed that the vision-based technique was more stable and reliable compared to the data glove-based technique. Hand gestures are obtained by evaluating the contour captured from the image segmentation using a glove worn by the speaker in Rosalina et al (2017). Also, in Danling, Yuanlong & Huaping (2016) they used a novel data glove called YoBu to collect data for gesture recognition.…”
Section: Gesture Acquisition Methodsmentioning
confidence: 99%
“…The work of Haitham, Alaa & Sabah (2017), Weiguo et al (2017), Rosalina et al (2017), , , Shunzhan et al (2017), Erhan, Hakan & Baran (2017), Vladislava, Predrag & Goran (2016), Deepali & Milind (2016) and Ananta & Piyanuch (2016) proposed using Artificial Neural Networks (ANN) for classification, whereas in and SoftMax output layer was used with feedforward ANN; in Shunzhan et al (2017), Erhan, Hakan & Baran (2017), Alvi, Fatema & Mohammad (2016), Vladislava, Predrag & Goran (2016); Deepali & Milind (2016) and Ananta & Piyanuch (2016) backpropagation training methods were used, and the authors in Jessie et al (2016) used Kohonen selforganizing maps as a type of ANN to classify data sets in unsupervised manner to convert hand gestures into Filipino words.…”
Section: Classification Of Hand Gesturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Khotimah et al implemented weighted k-nearest neighbor classification for dynamic sign language recognition [11]. Rosalina et al used artificial intelligence to recognize SIBI [12]. Other studies utilized Hidden Markov Model [13] and Naïve Bayes [14] methods.…”
Section: Introductionmentioning
confidence: 99%